2000
DOI: 10.1073/pnas.97.7.3771
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hippocampal activity by using purposeful behavior: Place navigation induces place cell discharge in both task-relevant and task-irrelevant spatial reference frames

Abstract: Continuous rotation of an arena in a cue-rich room dissociates the stationary room-bound information from the rotating arenabound information. This disrupted spatial discharge in the majority of place cells from rats trained to collect randomly scattered food. In contrast, most place cell firing patterns recorded from rats trained to solve a navigation task on the rotating arena were preserved during the rotation. Spatial discharge was preserved in both the task-relevant stationary and the task-irrelevant rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 36 publications
10
43
0
Order By: Relevance
“…When the animal is put back in the environment, an unspecified recognition process decides whether the current surroundings are familiar or novel. We imagine that the decision rules are very complex and depend on the behavioral requirements in the environment as well as the immediate sensory information (Markus et al 1995; Zinyuk et al 2000). We do not consider further what happens if a new template must be built.…”
Section: Discussionmentioning
confidence: 99%
“…When the animal is put back in the environment, an unspecified recognition process decides whether the current surroundings are familiar or novel. We imagine that the decision rules are very complex and depend on the behavioral requirements in the environment as well as the immediate sensory information (Markus et al 1995; Zinyuk et al 2000). We do not consider further what happens if a new template must be built.…”
Section: Discussionmentioning
confidence: 99%
“…Place preference navigation (Rossier et al, 2000) training on the rotating arena increased the prevalence of room frame-specific and conjunctive room and arena frame-specific place cell discharge patterns in response to continuous rotation. Disorganized responses were reduced by navigation training, and this acquired "frame specificity" was preserved when the rats were no longer navigating (Zinyuk et al, 2000;Fenton et al, 2002), suggesting that at the level of cellular behavior, the separate representation of room and arena information is acquired during place learning on a rotating arena. Similarly, Bostock et al (1991), Lever et al (2002), and Hayman et al (2003) demonstrated that place cell remapping developed with experience, indicating neural stimulus separation is also an acquired property.…”
Section: Segregation and Representation-distinct Hippocampal Functionsmentioning
confidence: 99%
“…They cannot use substratal idiothesis (40) or the arena-based cues that support it because the rotation makes this arena-based coordinate frame unstable with respect to the to-be-avoided sector. Nonetheless, the rats are probably aware of this arena information because the discharge of some hippocampal place cells remains organized in the arena frame during rotation despite explicitly training the rat to solve a room-frame defined allothetic place preference task (11). A key difference between the active allothetic avoidance and the standard water maze tasks is that in the dry arena, but not the water maze, there is a supply of substrate-anchored olfactory and tactile marks as well as the idiothesis they support.…”
Section: A Specific Role Of the Hippocampus In Organizing Informationmentioning
confidence: 99%